Time use and foraging behaviour in pre-breeding dabbling ducks Anas spp. in sub-arctic Norway - Céline Arzel; Johan Elmberg (Springer Berlin Heidelberg, 2022)
We studied time budgets and foraging methods in pre-breeding Mallard Anas platyrhynchos, (Eurasian) Teal Anas crecca, Wigeon Anas penelope, Pintail Anas acuta, Shoveler Anas clypeata and Gadwall Anas strepera in subarctic Norway in May. Among all six species studied, foraging accounted for the most common use of time, ranging from 19 % in male Pintail to 40–60 % in female Mallard, Teal, Pintail and Gadwall. Comfort behaviours amounted to 20–34 % of the time budget, and interaction and disturbance were marginal. Vigilance time ranged from 8 % in female Mallard to 20 % in male Pintail. Movement amounted to some 20 % of the time in most species and sexes. In Wigeon, sexes did not differ in time use, whereas in Mallard, Pintail and, in particular, Teal, females foraged more and engaged less in vigilance and interactions than did males. In addition, Teal and Mallard males engaged in the riskier foraging methods less than females, but more in those permitting vigilance. Although overlap in feeding methods was large among these species, Mallard and Teal were generalists, feeding at all depths, Wigeon foraged mainly in shallow water and Pintail foraged essentially in deep water. Our results support the income/capital breeder hypothesis with respect to males only; compared to lighter species, heavier species allocated less time to foraging but more to vigilance. We found no support for the hypothesis that long-distance migrants forage more to compensate for energy loss due to migratory flight. Foraging time in females was related to breeding phenology; early nesters spent more time feeding than later nesters.